EXPLORING STRATEGIES TO ENHANCE ISLAMIC BANKING’S ROLE TO RAISE CASH WAQF FUNDS - Rizanti Khairunisa; Nashr Akbar; Abrista Devi (IQTISHADIA, 2017)
Cash Waqf funds has an important role to empower the economy of Ummah. Unfortunately, the collected cashwaqf fund is still very small compared to its potentialnumber. Against this background, this researchaims to design systems that may enchance the role ofIslamic banks in cash waqf fund raising. This paperemployed Interpretative Structural Modeling (ISM) byconducting literature studies and In-depth interviewswith some regulators, practitioners and academicians.The result shows that experts and practitioners agreedthat the strong legal support on cash waqf is necessaryto enhance the role of Islamic Banks to raise cash waqffunds. It creates a sense of secure to the stakeholders.Furthermore, it requires a strong coordination betweenIndonesian Waqf Board (BWI), Ministry of ReligiousAffairs, Bank Indonesia (BI), Financial ServicesAuthority (OJK), Nazhir and Islamic FinancialInstitutions that may receive cash waqf (LKS-PWU)in order to boost the role of Islamic Banks. The mainobstacle that must be tacled soon is the lack of educationabout cash waqf.